THE EFFECTIVENESS OF DUOLINGO AS A MEDIA TO HELP TRANSLATING NARRATIVE TEXTS - Aditia, Kristina; dinata, juniarta panyugu; pamera, fasia friska; tawarik, oxtapianus (English Language Education Study Program, 2025)
Technology plays an important role in learning, including in the field of text translation in higher education. This study aims to analyze the effectiveness of the Duolingo application in improving the ability of third-semester students of University of Katolik Santo Agustinus Hippo in helping to translate narrative texts from Indonesian to English. The method used was a pre-experiment with a pre-test and post-test design. The research sample consisted of 25 students selected using the cluster random sampling technique. Data were collected through a translation test and analyzed using the T test on the SPSS application. The results showed a significant increase in the average score from the pre-test 58.60 to the post-test 78.80. The T test produced a value of 57.52, greater than the T table value of 2.064, which proves the effectiveness of the Duolingo application. This application helps students understand sentence structure, expand vocabulary, and recognize cultural contexts in the target language. The conclusion of this study is that the use of Duolingo can significantly help improve students' translation skills. It is recommended to integrate this application as a routine learning medium, especially in developing translation skills.